Taxonomic Confirmation of Rare Fruits in West Kalimantan Using rbcL and matK Sequences (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Phylogenetic analysis for plants can be very helpful in determining species identification or taxonomic status morphologically. rbcL and matK are widely used as genetic markers in constructing seed plant phylogenies. Different identification and new collection during the re-inventory from the previous study were found in two and four types of rare fruits in Sibohe Forest, West Kalimantan. The six types include pisang karok (Musa sp.) and Kandis (Garcinia sp.), as well as nubik (Artocarpus sp.), tehengan (Artocarpus sp.), smallest arok (Ficus sp.), and amok (Alpinia sp.). This study aimed to analyze the phenetic relationship of six rare fruits from Kalimantan based on rbcL and matK genes. DNA samples were obtained from dried body parts of the previous study and amplified by PCR using both forward and reverse primers for rbcL and matK genes. Amplification was observed on electrophoresis gel for rbcL gene of nubik, tehengan, smallest arok, amok, and pisang karok, while only pisang karok in matK gene. However, matK gene sequence was also obtained for amok even though the band was not seen on the gel. Phylogenetic analysis using the two genes confirmed the morphological identification reported in the previous study; however, using matK as a single gene for taxonomic confirmation must be reconsidered. The information of rbcL and matK sequences of six rare fruits from West Kalimantan could be the first information for building the DNA barcodes of the rare fruits in West Kalimantan.